Analysis of rotor slot width influence on a bearingless induction motor. (January 2020) - Ding, Qifeng; Yang, Zebin; Sun, Xiaodong; Zhao, Qian; Zhu, Huimin
Abstract: A bearingless induction motor (BIM) is a new type of motor with non-contact rotor suspension and negligible friction loss. One major imperfection of this motor is that its performance highly depends on the rotor slot width. This paper attempts to solve this problem by using a combined analytical method and finite element analysis method (FEM). Firstly, the influence on the motor starting characteristics is revealed by analytical method and verified by finite element simulation. Secondly, using the fast Fourier transform (FFT), the effect on the radial harmonic magnetic field distribution of air gap is analyzed. Meanwhile, the impact on the motor load performance is calculated. Thirdly, the relationship among the rotor slot width, the suspension force and the unbalanced magnetic pull force is explored. Finally, the simulation and experimental results show that the BIM designed by the combined analytical method and finite element calculation can not only obtain good torque characteristics and suspension performance but also has less load loss and a better accuracy in its mathematical model. This paper provides a theoretical basis and means for further design optimization of this type of motor.